Non-performance of the Severance Pay Program in Slovenia - Vodopivec, Milan (2012)
Combining information from the Firm Survey of Labor Costs with the information about claims filed with the Guarantee Fund by workers whose employers defaulted on their severance pay obligations, the paper analyzes the so-called non-performance problem of severance pay--the fact that coverage, and thus legal entitlement, does not guarantee the actual receipt of the benefit--as experienced in Slovenia in 2000. The findings are threefold: (i) one-third of total obligations incurred by firms failed to be honored and only a small portion of defaulted severance pay claims were reimbursed by the Guarantee Fund; (ii) while both men and women seem to be equally affected, workers older than 40 were disproportionally represented among those whose severance pay claims failed to be honored; and, (iii) among firms that incurred severance pay liabilities, larger and more productive firms were more likely to observe their fiduciary obligations and pay them out. These findings corroborate the weaknesses of severance pay as an income protection program, pointing to the large scale of the non-performance problem and the inequities created by it.